Cdc42 controls spindle orientation to position the apical surface during epithelial morphogenesis - Jaffe, Aron B. (The Rockefeller University Press, 2008)
The establishment of apical–basal polarity within a single cell and throughout a growing tissue is a key feature of epithelial morphogenesis. To examine the underlying mechanisms, the human intestinal epithelial cell line Caco-2 was grown in a three-dimensional matrix to generate a cystlike structure, where the apical surface of each epithelial cell faces a fluid-filled central lumen. A discrete apical domain is established as early as the first cell division and between the two daughter cells. During subsequent cell divisions, the apical domain of each daughter cell is maintained at the center of the growing structure through a combination of mitotic spindle orientation and asymmetric abscission. Depletion of Cdc42 does not prevent the establishment of apical–basal polarity in individual cells but rather disrupts spindle orientation, leading to inappropriate positioning of apical surfaces within the cyst. We conclude that Cdc42 regulates epithelial tissue morphogenesis by controlling spindle orientation during cell division.